Pengaruh Penambahan Pati Beras dan Jeda Pengisian Gips Terhadap Stabilitas Dimensi Alginat - Tenia Yohana Oktaviana; Oedijani Santoso; Gunawan Wibisono; Lusiana Batubara (Jurnal Material Kedokteran Gigi, 2021)
Alginate is an impression material that is widely used in dentistry but lacks dimensional stability. The time delay for filling in the gypsum is also one of the things that causes a change in the dimensional stability. Natural starch can be found in plants, one of which is rice, which is often found. Starch and alginate can both undergo a gelatinization process so that starch can be used as an alginate mixture. This study aims to determine the effect of adding rice starch to the alginate printing material and the time delay for filling the gypsum on the dimensional stability of the printed output. This research wass a laboratory experimental study using a post-test only control group design. The sample of this study consisted of 36 samples divided into 12 groups. Measurement of the dimensional stability of the printed output was carried out using a digital caliper. The data were analyzed by means of the Two-Way ANOVA test. The results showed that the mean percentage change in the dimensions of the treatment group was smaller than the control group. The results of the Two-Way ANOVA test showed significant results (p <0.05) on the effect of the concentration of rice starch in the alginate printing material on the dimensional stability of the printouts, while the effect of the time delay for filling the gypsum on the dimensional stability of the printed results showed insignificant results (p>0,05). There was an interaction between the concentration of rice starch added and the time delay for filling the gypsum on the dimensional stability of the printouts (p <0.05).